Literasi Digital: Sebuah Tinjauan Sistematis - Dewi Lestari; Muhammad Jufri; Perengki Susanto (Jurnal Teknik Ibnu Sina (JT-IBSI), 2025)
The purpose of this article is to identify and analyze several references on the keyword digital literacy. Through Harzing's Publish or Perish, literature systematization was carried out for this study by utilizing the Scopus database. Using the SPAR-4-SLR Protocol, data analysis was carried out using Microsoft Excel, Mendeley, and Vos Viewer to provide transparency and replication. The results of this study identified 50 primary articles indexed in Scopus Q1 based on Scimago Journal Ranking (SJR). This study also found 6 knowledge clusters that support research on digital literacy with a total link strength of 55. Vos Viewer visualization revealed that "Digital Literacy" has a significant magnitude and is related to the phrase "Information Literacy and Digital Transformation" showing a clear relationship. This study has several limitations, such as obstacles in accessing databases that are limited to Scopus. Therefore, it is recommended that further research expand its data collection by using additional sources such as Emerald, SpringerLink, ScienceDirect, Eb-sco, Google Scholar, ProQuest, and non-Q journals such as Web of Science.